Investigation of capacitive deionization process parameters on salt adsorption capacity via experimental design approach - Acikgul, Demet; Duranoglu, Dilek (IOP Publishing Ltd, 2024)
Process parameters of Capacitive Deionization (CDI) was investigated and optimized in this study. The effect of adsorption period (7-13 min), flow rate (5-20 ml min(-1)), and NaCl concentration (2-22 mM) on salt adsorption capacity was examined via Box-Behnken experimental design approach. A quadratic regression model (R-2 = 0.9987) was developed, revealing significant individual and binary effects between process parameters and salt adsorption capacity. The ANOVA results demonstrated its high significance with the p-value<0.0001. Optimal conditions varied with salt concentration, indicating significant interactions between the parameters. Maximum salt adsorption capacity occurred at 5 ml min(-1) flow rate and 13 min adsorption period for 22 mM NaCl, whereas for 12 mM and 2 mM NaCl concentrations, maximum adsorption capacity was obtained at the flow rate of 20 ml min(-1) and duration of 13 min. This study provided deep insights into CDI modelling and optimization, crucial for water treatment advancements.
Keywords: capacitive deionization; optimization; modelling; box behnken experimental design; ACTIVATED CARBON; WATER DESALINATION; ELECTRODES; Physics